Intergenerational Long Term Effects of Preschool: Structural Estimates from a Discrete Dynamic Programming Model - James J. Heckman; Lakshmi Kanta Raut (Institute for the Study of Labor (IZA), 2013)
This paper formulates a structural dynamic programming model of preschool investment choices of altruistic parents and then empirically estimates the structural parameters of the model using the NLSY79 data. The paper finds that preschool investment significantly boosts cognitive and non-cognitive skills, which enhance earnings and school outcomes. It also finds that a standard Mincer earnings function, by omitting measures of non-cognitive skills on the right hand side, overestimates the rate of return to schooling. From the estimated equilibrium Markov process, the paper studies the nature of within generation earnings distribution and intergenerational earnings and schooling mobility. The paper finds that a tax financed free preschool program for the children of poor socioeconomic status generates positive net gains to the society in terms of average earnings and higher intergenerational earnings and schooling mobility.
Keywords: J24; J62; O15; I21; 330; preschool investment; early childhood development; intergenerational social mobility; structural dynamic programming; Frühkindliche Bildung; Wirkungsanalyse; Intergenerationale Übertragung; Soziale Mobilität; Dynamische Optimierung; Schätzung; USA